Rural "exchange": an approach to multi-use and inter-disciplinary creation of space in a rural community environment - Webb, Jonathan (My University, 2011)
With the urbanization of Modern society, much emphasis has been placed on communities living in or around cities, while the communities living in the rural environment are left, on the whole, ignored. The polar development and historic culture of colonial city development has left the most fragile sect of developing nations, most without the development drivers so badly needed. The rapidly growing divide between the urban and the rural environment, is evident with the functions and forms within the buildings in such areas. The common trait of transplanting an urban system of function and building into a rural environment needs to be addressed. Using a building as a catalyst of development and place-making in a certain area, to a certain community, is explored in this thesis. While the building acts as a agent for, and with the community, it is also a connection to the urbanization environment. The space ‘in-between’ is explored, bring the rural and urban in connection to each other , both in form, function and connections. The building forms an envelope, in-which program is placed, yet the connections of those functions create ‘exchanges’, in the sense of physical space, rural-urban connections and personality inter-changes, all which reduces overall size of form, and creating a truly diverse and multi-use platform on which the community can connect